AMBISI DALAM MENDORONG PERGOLAKAN KEPRIBADIAN TOKOH-TOKOH DALAM NOVEL THE PEARL KARYA STEINBECK - Nida Zahirah; Fransiska Dwi Srikandi; Anisa Nur Hidayanti; Nur Lidya; Mutmainnah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research analyzes the personality of the characters in The Pearl by John Steinbeck using Sigmund Freud's Psychoanalytic Theory (id, ego, and superego). Through qualitative methods and text analysis, it was found that Kino's id drives impulsive and aggressive actions in defending the pearl, while the ego attempts to channel these desires in a more realistic direction. The superego, which plays a role in maintaining morality, is often overshadowed by materialistic impulses. The conflict between Kino's id, ego, and superego reflects the struggle between personal ambition and moral values in human life.